2023
DOI: 10.1177/13506501221147988
|View full text |Cite
|
Sign up to set email alerts
|

Influence of contacting shape of partial wear on friction properties of copper-based materials for trains

Abstract: In view of the fact that the contact between the pad and the disc cannot match perfectly in the actual braking process, the influence of contacting shape on the tribological performance was studied. Four copper-based brake pads in ratio (radial dimension / circumferential dimension) of 0.4, 0.6, 0.8 and 1.2 were used to perform contacting shape test on a small-scaled braking dynamometer at speeds 60 km/h, 100 km/h, 140 km/h and 180 km/h and contact pressure 0.5 MPa. The results indicated that contacting shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…3 On the micro-scale, the increase of temperature will lead to the change of material properties in the contact zone, which will affect the contact behavior between the asperity and the friction and wear process. 4 Therefore, extensive investigations have been conducted to clarify the factors that are relevant to the brake disc temperature field, such as brake disc material and structure, 58 brake pad material, 912 shape, 1315 and arrangement pattern. 1618 Results demonstrated that, the brake pad shape and arrangement pattern cause the difference of distribution of friction arc length and brake force, which affects significantly the thermal distribution on the disc.…”
Section: Introductionmentioning
confidence: 99%
“…3 On the micro-scale, the increase of temperature will lead to the change of material properties in the contact zone, which will affect the contact behavior between the asperity and the friction and wear process. 4 Therefore, extensive investigations have been conducted to clarify the factors that are relevant to the brake disc temperature field, such as brake disc material and structure, 58 brake pad material, 912 shape, 1315 and arrangement pattern. 1618 Results demonstrated that, the brake pad shape and arrangement pattern cause the difference of distribution of friction arc length and brake force, which affects significantly the thermal distribution on the disc.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 9 developed a coupled heat-structure model in order to simulate and investigate the temperature field and contact pressure distribution of brake pads with varying wear patterns during emergency braking scenarios. Han 10 and Xiang 11 conducted tests and finite element simulation studies on the relationship between the braking pad structure and the braking disc temperature of high-speed trains and discovered that the tribological behaviors of the braking interface are significantly affected by the braking pad structure. Hatam 12 presented an approach for the finite element modeling of wear based on the Archard wear equation and conducted experiments to validate its accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Ghatrehsamani 24 developed a model capable of predicting the variation of the aforementioned parameters by use of AWM model. Han et al 25 studied the influence of contacting shape on the tribological performance, the influence of contacting shape on the tribological performance. Jiang 26 studied the wear behaviors and mechanisms of AISI H13 steel as a function of sliding speed and hardness, through investigating morphologies, compositions, and phases of worn surfaces.…”
Section: Introductionmentioning
confidence: 99%